Adz Dzikraa: terjemah dan tafsir Al qur'an dalam huruf Arab dan Latin J - Bachtiar Surin (Angkasa, 1991)
Oen, Jil. 6(Jz.26-30)=c.1,ws.jl.5.[jz.21-25].c.1/ir, jil.4(juz 16-20),c.1/tr, jil.1=c.1; jil.2=c.1; jil.5=c.2; jil.6=c.1